A Mathematical Model Toward Energy Optimization with Building-Integrated Photovoltaics. Issue 1 (1st May 2017) - Araji, Mohamad T.; Shahid, Iqbal
Abstract : This paper presents a new mathematical model for quantification of photovoltaics performance as a function of the building form. It involves an algorithm suited for preliminary concept phase analysis, which serves to aid in designing optimum number of floors with a net zero energy rating. Performance per program area indicated an energy decrease with footprint and increase with aspect ratio for a fixed volume. As the ratio of façade surface area to roof surface area increases with the building height, different scenarios were examined to measure this correlation. The applicability and utility of the current model extend to more complex façade forms and geometries.